Analysis of the Need for Development of Virtual Reality-Based Learning Media to Build Technological Pedagogical and Content Knowledge (TPACK) Competencies for Prospective Physics Teachers - Fajrul Wahdi Ginting; Halimatus Sakdiah; Widya; Ratna Unaida (Jurnal Penelitian Pendidikan IPA, 2023)
Technological Pedagogical and Content Knowledge (TPACK) is a conceptual framework used to describe the knowledge needed by a teacher to integrate technology into the learning process. In the context of developing Virtual Reality (VR) based learning media, physics education students as prospective teachers need to have a strong understanding of how VR technology can be used as a medium for teaching specific topics (TK), how to actively involve students in the VR environment ( PK), and a deep understanding of the lesson topics taught (CK). This research aims to produce Virtual Reality-Based Learning Media to build the TPACK competency of Physics Teacher Candidates that is feasible, practical, and effective. The development research method used is EDR (Educational Design Research) with the following stages: analysis and exploration; design and construction; and evaluation and reflection. Based on the questionnaire given to students, interviews conducted with lecturers, and literature review studies that have been carried out, it was concluded that it is necessary to develop Virtual Reality-based Learning Media Development to Build the Technological Pedagogical and Content Knowledge (TPACK) Competencies of Prospective Physics Teachers.